Echinacea аngustifolia L. МОРФОЛОГИЯЛЫҚ ЕРЕКШЕЛIКТЕРІ МЕН АНАТОМИЯЛЫҚ ҚҰРЫЛЫСЫ (Experimental biology, 2009)
For the first time in conditions of Southern Kazakhstan carried out morphological and anatomic researches of two kinds Echinacea anqustifolia L.
Keywords: Echinacea anqustifolia L